The Effect of Training and Competence of Human Resources on Employee Performance in an Islamic Perspective (Case Study of the Trade and Cooperative Office of Labuhan Batu Utara Regency) - Srika Aryunita; Dahrani Dahrani (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Performance refers to work achievement. Training helps employees improve their skills and knowledge, especially when learning and experience are lacking. In an Islamic perspective, performance includes not only results but also intentions, processes, ethics, and societal impact. Employees who work with sincerity, trustworthiness, and professionalism will receive blessings in both life and work. Surah At-Tin (4) encourages people to utilize Allah's gifts, which means being grateful and making the best use of resources. The issue in this study is the impact of human resource (HR) performance and competence on employee performance at the Trade and Cooperatives Service of North Labuhan Batu Regency. Effective training and competency development are essential for improving employee performance and achieving organizational goals. A lack of competence negatively affects performance, which in turn impacts government development and the institution’s reputation. This study aims to examine the effect of training and HR competence on employee performance, both individually and together. The findings show that 57.6% of employee performance is influenced by training and HR competence. Employee performance is crucial as it determines their contribution to the organization and, ultimately, national development.